2016
DOI: 10.21273/horttech.26.3.309
|View full text |Cite
|
Sign up to set email alerts
|

Saline Irrigation Affects Growth and Leaf Tissue Nutrient Concentration of Three Native Landscape Plant Species

Abstract: Greywater is a renewable irrigation alternative to potable water; however, its use as an irrigation source is limited by the potential for salt injury to plants. Research was conducted to determine salt tolerance of three common landscape species, small anise tree (Illicium parviflorum), ‘Henry’s Garnet’ sweetspire (Itea virginica), and muhly grass (Muhlenbergia capillaris). Two experiments were performed, one with high so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 7 publications
2
10
2
Order By: Relevance
“…To the best of our knowledge, there were no reports of the leaf Na + concentrations of E. spectabilis and S. scoparium irrigated with saline water irrigation. However, the values recorded in our study were much less than those reported by LeCompte et al (2016), who found that pink muhly grass had 11.7 to 31.4 mg • g -1 Na + in the leaves when grown in a substrate (5 pinebark:3 peat:1 perlite) and irrigated with 4000 to 10,000 mg • L -1 NaCl (5.0-12.5 dS • m -1 ) for 15 weeks. The discrepancy in the leaf Na + concentrations in these studies might result from different plant species and different durations of saline water irrigation.…”
Section: Speciescontrasting
confidence: 91%
See 4 more Smart Citations
“…To the best of our knowledge, there were no reports of the leaf Na + concentrations of E. spectabilis and S. scoparium irrigated with saline water irrigation. However, the values recorded in our study were much less than those reported by LeCompte et al (2016), who found that pink muhly grass had 11.7 to 31.4 mg • g -1 Na + in the leaves when grown in a substrate (5 pinebark:3 peat:1 perlite) and irrigated with 4000 to 10,000 mg • L -1 NaCl (5.0-12.5 dS • m -1 ) for 15 weeks. The discrepancy in the leaf Na + concentrations in these studies might result from different plant species and different durations of saline water irrigation.…”
Section: Speciescontrasting
confidence: 91%
“…Pink muhly grass irrigated with 2000 to 4000 mg • L -1 NaCl (EC, 2.5-5.0 dS • m -1 ) had 15.6 to 17.4 mg • g -1 Clions in the leaves (LeCompte et al, 2016). These values are similar to or slightly greater than our results.…”
Section: Speciessupporting
confidence: 83%
See 3 more Smart Citations